Impact of xerostomia on dysphagia after chemotherapy–intensity‐modulated radiotherapy for oropharyngeal cancer: Prospective longitudinal study. (25th November 2015) - Vainshtein, Jeffrey M.; Samuels, Stuart; Tao, Yebin; Lyden, Teresa; Haxer, Marc; Spector, Matthew; Schipper, Matthew; Eisbruch, Avraham
Abstract: Background: The purpose of this study was to assess how xerostomia affects dysphagia. Methods: Prospective longitudinal studies of 93 patients with oropharyngeal cancer treated with definitive chemotherapy–intensity‐modulated radiotherapy (IMRT). Observer‐rated dysphagia (ORD), patient‐reported dysphagia (PRD), and patient‐reported xerostomia (PRX) assessment of the swallowing mechanics by videofluoroscopy (videofluoroscopy score), and salivary flow rates, were prospectively assessed from pretherapy through 2 years. Results: ORD grades ≥2 were rare and therefore not modeled. Of patients with no/mild videofluoroscopy abnormalities, a substantial proportion had PRD that peaked 3 months posttherapy and subsequently improved. Through 2 years, highly significant correlations were observed between PRX and PRD scores for all patients, including those with no/mild videofluoroscopy abnormalities. Both PRX and videofluoroscopy scores were highly significantly associated with PRD. On multivariate analysis, PRX score was a stronger predictor of PRD than the videofluoroscopy score. Conclusion: Xerostomia contributes significantly to PRD. Efforts to further decrease xerostomia, in addition to sparing parotid glands, may translate into improvements in PRD. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1605–E1612, 2016